Synthesis Of Mcm-41 Nanomaterial From Algerian Bentonite: Influence Of Synthesis Ph - Ali-dahmane, T.; Brahmi, L.; Hamacha, R.; Villieras, F.; Bengueddach, A. (University of Eloued جامعة الوادي, 2017)
Mesoporous materials of the MCM-41 type were synthesized from Algerian bentonite as an aluminosilicate source without the addition of pure silica and aluminum reagents. The samples were synthesized under hydrothermal condition using cetyltrimithylammonium bromide (CTAB) as surfactant. The influence of initial synthesis pH on the material properties of as-synthesis MCM-41 samples was studied at different temperatures of crystallization. The samples were characterized using several techniques e.g. X-ray diffraction (XRD), N2 adsorption-desorption and transmission electron microscope (TEM). The experimental results showed that bentonite can be used as an aluminosilicate source for the synthesis of Al-MCM-41. By decreasing the synthesis temperature of crystallization, it is necessary to decrease the synthesis pH value to form the best ordered hexagonal phase and eliminate the lamellar phase.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 02
Keywords: bentonite; alkaline fusion; pH; Al-MCM-41.